Pathological mutations differentially affect the self-assembly and polymerisation of the innate immune system signalling adaptor molecule MyD88 - Ailís O’Carroll; Brieuc Chauvin; James W. P. Brown; Ava Meagher; Joanne Coyle; Jurgen Schill; Akshay Bhumkhar; Dominic J. B. Hunter; Thomas Ve; Bostjan Kobe; Emma Sierecki; Yann Gambin (BMC Biology, 2018)
Abstract Background Higher-order self-assembly of proteins, or “prion-like” polymerisation, is now emerging as a simple and robust mechanism for signal amplification, in particular within the innate immune system, where the recognition of pathogens or danger-associated molecular patterns needs to trigger a strong, binary response within cells. MyD88, an important adaptor protein downstream of TLRs, is one of the most recent candidates for involvement in signalling by higher order self-assembly. In this new light, we set out to re-interpret the role of polymerisation in MyD88-related diseases and study the impact of disease-associated point mutations L93P, R196C, and L252P/L265P at the molecular level. Results We first developed new in vitro strategies to characterise the behaviour of polymerising, full-length MyD88 at physiological levels. To this end, we used single-molecule fluorescence fluctuation spectroscopy coupled to a eukaryotic cell-free protein expression system. We were then able to explore the polymerisation propensity of full-length MyD88, at low protein concentration and without purification, and compare it to the behaviours of the isolated TIR domain and death domain that have been shown to have self-assembly properties on their own. These experiments demonstrate that the presence of both domains is required to cooperatively lead to efficient polymerisation of the protein. We then characterised three pathological mutants of MyD88. Conclusion We discovered that all mutations block the ability of MyD88 to polymerise fully. Interestingly, we show that, in contrast to L93P and R196C, L252P is a gain-of-function mutation, which allows the MyD88 mutant to form extremely stable oligomers, even at low nanomolar concentrations. Thus, our results shed new light on the digital “all-or-none” responses by the myddosomes and the behaviour of the oncogenic mutations of MyD88.